The Effects of Metformin and Weight Loss on Biomarkers Associated With Breast Cancer Outcomes. (18th May 2018) - Patterson, Ruth E; Marinac, Catherine R; Sears, Dorothy D; Kerr, Jacqueline; Hartman, Sheri J; Cadmus-Bertram, Lisa; Villaseñor, Adriana; Flatt, Shirley W; Godbole, Suneeta; Li, Hongying; Laughlin, Gail A; Oratowski-Coleman, Jesica; et al.
Abstract: Background: This study investigated the effects of metformin and weight loss on biomarkers associated with breast cancer prognosis. Methods: Overweight/obese postmenopausal breast cancer survivors (n = 333) were randomly assigned to metformin vs placebo and to a weight loss intervention vs control (ie, usual care). The 2 × 2 factorial design allows a single randomized trial to investigate the effect of two factors and interactions between them. Outcomes were changes in fasting insulin, glucose, C-reactive protein (CRP), estradiol, testosterone, and sex-hormone binding globulin (SHBG). The trial was powered for a main effects analysis of metformin vs placebo and weight loss vs control. All tests of statistical significance were two-sided. Results: A total of 313 women (94.0%) completed the six-month trial. High prescription adherence (ie, ≥80% of pills taken) ranged from 65.9% of participants in the metformin group to 81.3% of those in the placebo group ( P < .002). Mean percent weight loss was statistically significantly higher in the weight loss group (–5.5%, 95% confidence interval [CI] = –6.3% to –4.8%) compared with the control group (–2.7%, 95% CI = –3.5% to –1.9%). Statistically significant group differences (ie, percent change in metformin group minus placebo group) were –7.9% (95% CI = –15.0% to –0.8%) for insulin, –10.0% (95% CI = –18.5% to –1.5%) for estradiol, –9.5% (95% CI = –15.2% to –3.8%) for testosterone, and 7.5% (95% CI = 2.4% to 12.6%) for SHBG. Statistically significant group differences (ie, percent change in weight loss group minus placebo group) were –12.5% (95% CI = –19.6% to –5.3%) for insulin and 5.3% (95% CI = 0.2% to 10.4%) for SHBG. Conclusions: As adjuvant therapy, weight loss and metformin were found to be a safe combination strategy that modestly lowered estrogen levels and advantageously affected other biomarkers thought to be on the pathway for reducing breast cancer recurrence and mortality.